2015
DOI: 10.1128/jvi.02791-14
|View full text |Cite
|
Sign up to set email alerts
|

The Stress Granule Protein G3BP1 Recruits Protein Kinase R To Promote Multiple Innate Immune Antiviral Responses

Abstract: Stress granules (SGs) are cytoplasmic storage sites containing translationally silenced mRNPs that can be released to resume translation after stress subsides. We previously showed that poliovirus 3C proteinase cleaves the SG-nucleating protein G3BP1, blocking the ability of cells to form SGs late in infection. Many other viruses also target G3BP1 and inhibit SG formation, but the reasons why these functions evolved are unclear. Previously, we also showed a link between G3BP1-induced SGs and protein kinase R (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
193
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(205 citation statements)
references
References 52 publications
9
193
3
Order By: Relevance
“…For example, pattern recognition receptors like RIG-I are activated upon binding to viral RNAs in SGs, which leads to the stimulation of interferon-related genes (42,43,82). Alternatively, recent studies suggest that in the absence of virus infection, SGs can activate innate immune signaling (11,83,84). Overexpression of G3BP, which leads to SG assembly, recruits and activates PKR within SGs in a novel manner whereby PKR dimerization and viral RNA are not required.…”
Section: Discussionmentioning
confidence: 99%
“…For example, pattern recognition receptors like RIG-I are activated upon binding to viral RNAs in SGs, which leads to the stimulation of interferon-related genes (42,43,82). Alternatively, recent studies suggest that in the absence of virus infection, SGs can activate innate immune signaling (11,83,84). Overexpression of G3BP, which leads to SG assembly, recruits and activates PKR within SGs in a novel manner whereby PKR dimerization and viral RNA are not required.…”
Section: Discussionmentioning
confidence: 99%
“…Proximity ligation assays were performed as previously described (55). Briefly, cells were stressed with arsenite, allowed to recover, and then fixed with 4% formaldehyde.…”
Section: Methodsmentioning
confidence: 99%
“…For experiments in which high resolution was not necessary, a standard epifluorescence Nikon TE2000 microscope was used. Previously published procedures were followed for sample processing (55,58). The antibodies used for microscopy were as follows: goat anti-CK2␣ (Santa Cruz), rabbit anti-CK2␣= (Bethyl), mouse anti-CK2␤ (Santa Cruz), goat anti-TIA1 (Santa Cruz), rabbit anti-G3BP1 (56), rabbit anti-eIF4G (59), rabbit anti-PKR (ProSci), and mouse anti-Flag (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…However, it is important to bear in mind that SGs are being increasingly viewed as more than a mere consequence of a cell's stress response or a temporary storage depot for mRNPs. Two independent research groups have shown that SGs can promote innate immune responses (76)(77)(78)(79). This has led to the proposal that SGs serve as platforms for recognizing and responding to viral infections (80), which may explain why so many viruses destroy or modify SGs during infection and necessitates a better understanding of SG biology.…”
Section: Discussionmentioning
confidence: 99%